Finite volume method for steady state 2D heat conduction in solids - John, Shana Elizabeth (Nanyang Technological University, 2023)
In this project, a finite volume formulation is developed to solve the 2D steady state heat conduction problem in a rectangular domain with different boundary conditions. First, the finite volume method is applied for Dirichlet boundary conditions and the respective discretised equations are derived. Next, the equations are solved using the iterative algorithm developed in MATLAB and the finite volume solution is validated using the analytical solution. The finite volume solution is found to converge to the analytical solution when the meshing is made finer. Subsequently, the MATLAB code is modified to incorporate Neumann and Robin Boundary conditions.